2014
DOI: 10.2174/1871527313666140806150440
|View full text |Cite
|
Sign up to set email alerts
|

Drugs Targeting SNPrs35753505 of the NRG1 Gene May Prevent the Association of Neurological Disorder Schizophrenia in a Pakistani Population

Abstract: The Neuregulin 1 (NRG1) gene has been associated with schizophrenia in several populations, and all four types of NRG1 genes are linked with neurotransmitters activities. In this study for the first time we have demonstrated an association between NRG1 mutation and schizophrenia in Pakistani population. We examined the relationship of three genetic variants SNPs: rs3924999, rs2954041 and rs35753505 of NRG1 gene with the onset of disease. Genomic DNA samples were obtained from the blood of 100 patients and 80 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…rs35753505 of NRG1 plays an important role in conferring susceptibility to the schizophrenia in a Pakistani population . Besides, alleles at the rs3924999 of the NRG1 gene increase the risk of schizophrenia .…”
Section: Resultsmentioning
confidence: 99%
“…rs35753505 of NRG1 plays an important role in conferring susceptibility to the schizophrenia in a Pakistani population . Besides, alleles at the rs3924999 of the NRG1 gene increase the risk of schizophrenia .…”
Section: Resultsmentioning
confidence: 99%
“…ErbB1 ligands, in particular, have been shown to negatively regulate GABAergic development in the neocortex and influence activity of glutamate receptor channels (Nagano et al 2007). In addition, genetic and candidate gene studies have implicated both ErbB1-4 and NRG1-6 in SZ (Barnes et al 2012; Deng et al 2013; Nawaz et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…However, published studies have demonstrated an association between NRG1 and TNF-α gene mutations and SCZ in the Pakistani population [81]. Earlier, Nawaz et al [14] and Naqvi et al [82] demonstrated that the NRG1 genetic variant SNP rs35753505 and polymorphism8nrg433E1006 plays an important role in conferring susceptibility to SCZ in the Pakistani population and may represent a potential antipsychotic drug target in such patients [15].Moreover, Amir et al provided strong evidence that supports the role of CACNA1C, GRM3, and DRD2 genes as schizophrenia susceptibility genes in the Pakistani population [74]. Nevertheless, one study has shown that some genetic variants rs1801028 and rs6277 of DRD2 are not associated with schizophrenia in the Pakistani population [83].…”
Section: Genetics Of Schizophreniamentioning
confidence: 96%
“…In addition to genetic makeup, various factors such as drug-addiction, underlie the predisposition toward SCZ. A large number of people in Pakistan, mostly men, are addicted to tobacco, cannabis, betel nut, charas, and other illicit drugs [14]. Repeated administration of these stimulants at a younger age (<15 years) increases the likelihood of developing SCZ [15].…”
Section: Prevalence Of Schizophreniamentioning
confidence: 99%